Perkembangan Kajian Ilmu-Ilmu Bayan Dalam Balaghah Al-Qur’an - Idris Siregar; Najwa Fathiah; Suci Aldina Prahastiwi; Adil Nazla Sipa Sinaga (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The study of Qur’anic balaghah plays an important role in revealing the beauty, precision, and depth of meaning of the language of revelation. One of its main branches, ʿilm al-bayan, focuses on modes of meaning expression through various rhetorical devices such as tashbih (simile), istiʿarah (metaphor), majaz (figurative expression), and kinayah (indirect expression), enabling Qur’anic verses to be understood not only literally but also rhetorically and contextually. This study aims to analyze the conceptual development of ʿilm al-bayan in Qur’anic balaghah from classical to contemporary perspectives in order to explain shifts in methodological orientation and its continuing relevance in modern Qur’anic studies. Employing a qualitative method through a systematic literature review of classical works, contemporary scholarly books, and peer-reviewed journal articles, this research examines the evolution of theories and analytical frameworks of ʿilm al-bayan. The findings indicate that ʿilm al-bayan functions as a crucial analytical instrument for elucidating the relationship between linguistic structure and the meaning of revelation, both in terms of aesthetic value and communicative function. Furthermore, the development of ʿilm al-bayan demonstrates a transition from a predominantly normative and descriptive approach toward a more contextual and interdisciplinary analysis. In conclusion, ʿilm al-bayan continues to hold a strategic position in the study of Qur’anic balaghah by bridging linguistic beauty and the normative meaning of revelation, thereby maintaining its relevance within contemporary Qur’anic scholarship.